2023
DOI: 10.3390/molecules28083531
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Biological Activity of PI3Kδ Inhibitor by the Introduction of a Fluorine Atom Using the Computational Workflow

Abstract: As a member of the class I PI3K family, phosphoinositide 3-kinase δ (PI3Kδ) is an important signaling biomolecule that controls immune cell differentiation, proliferation, migration, and survival. It also represents a potential and promising therapeutic approach for the management of numerous inflammatory and autoimmune diseases. We designed and assessed the biological activity of new fluorinated analogues of CPL302415, taking into account the therapeutic potential of our selective PI3K inhibitor and fluorine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It should be noted that the ALR2 inhibitors identified in this study were not as potent as reported in previous studies, despite having better docking scores, which can be attributed to the known limitation of these docking scoring functions to accurately predict binding affinities. While these docking methods can help discriminate between different ligands based on binding affinity, it is not clear whether they will succeed in biological evaluation. Nevertheless, the hits generated contain new chemotypes and unfold new avenues for further structural refinement in a hit-to-lead optimization process, thus consolidating them to be new ALR2 potent inhibitors in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the ALR2 inhibitors identified in this study were not as potent as reported in previous studies, despite having better docking scores, which can be attributed to the known limitation of these docking scoring functions to accurately predict binding affinities. While these docking methods can help discriminate between different ligands based on binding affinity, it is not clear whether they will succeed in biological evaluation. Nevertheless, the hits generated contain new chemotypes and unfold new avenues for further structural refinement in a hit-to-lead optimization process, thus consolidating them to be new ALR2 potent inhibitors in the future.…”
Section: Discussionmentioning
confidence: 99%